2017
DOI: 10.1155/2017/3762194
|View full text |Cite
|
Sign up to set email alerts
|

First-Line Helicobacter pylori Eradication in Patients with Chronic Kidney Diseases in Taiwan

Abstract: Aims Patients with chronic kidney disease (CKD) and Helicobacter pylori (H. pylori) infection have a higher incidence of gastroduodenal diseases and therefore are recommended to receive eradication therapies. This study aimed to assess the efficacy of a 7-day standard triple therapy in patients with CKD (eGFR < 60 ml/min/1.73 m2) and to investigate the clinical factors influencing the success of eradication. Methods A total of 758 patients with H. pylori infection receiving a 7-day standard first-line triple t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Following eradication therapy 84.3% of patients reported disease symptom resolution which was a bit lower than reported 91%[57]. Self-reported regimen completion was 94.3% in this study which was comparable with 95.7[58] and a bit lower than 99.8% reported elsewhere[59] and it has no significant influence on self-reported adverse effects. The response of patients showed that 84.3% of patients achieved complete resolution of acid-pepsin disorder symptoms.…”
Section: Discussionsupporting
confidence: 58%
“…Following eradication therapy 84.3% of patients reported disease symptom resolution which was a bit lower than reported 91%[57]. Self-reported regimen completion was 94.3% in this study which was comparable with 95.7[58] and a bit lower than 99.8% reported elsewhere[59] and it has no significant influence on self-reported adverse effects. The response of patients showed that 84.3% of patients achieved complete resolution of acid-pepsin disorder symptoms.…”
Section: Discussionsupporting
confidence: 58%
“…Liang et al in Taiwan reported a case-control study for 758 patients with H. pylori infection [7]. The eradication regimen was a 7-day standard triple therapy with a proton pump inhibitor (PPI), CAM, and AMPC.…”
Section: Background and Methods In Included Studiesmentioning
confidence: 99%
“…One study treated cases with normal CCr and was excluded [23]. After scrutiny, five papers were included in this systematic review [4][5][6][7][8] (Figure 1). There were two RCTs and three case-control studies.…”
Section: Literature Selectionmentioning
confidence: 99%
See 2 more Smart Citations